2008
DOI: 10.1029/2007sw000349
|View full text |Cite
|
Sign up to set email alerts
|

GPS scintillation in the high arctic associated with an auroral arc

Abstract: [1] A rapid signal-fading event produced by diffractive scintillations was observed around 0123 UT on 8 November 2004 by three closely sited (less than 250 m apart) GPS scintillation receivers in northern Norway. The entire duration of the event was about 10 s and was recorded by all three receivers. Intense, short duration events such as these are not clearly observable in the 1-min scintillation index (S4) because they do not necessarily last for the entire minute. In spite of their short duration they can c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(52 citation statements)
references
References 13 publications
1
49
0
2
Order By: Relevance
“…The scintillations are more common in the auroral oval during geomagnetic disturbed conditions and were registered close to the noon and the midnight (Spogli et al, 2009;Moen et al, 2013). Some authors found that the strong correlations between the GPS phase scintillation and fluctuations of optical auroral emissions is occurred during investigation of the auroral arcs (Kinrade et al, 2013;Smith et al, 2008). In the auroral ionosphere the increasing of the fluctuations intensity followed after the auroral activity was observed (Aarons, 1997;Shagimuratov et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The scintillations are more common in the auroral oval during geomagnetic disturbed conditions and were registered close to the noon and the midnight (Spogli et al, 2009;Moen et al, 2013). Some authors found that the strong correlations between the GPS phase scintillation and fluctuations of optical auroral emissions is occurred during investigation of the auroral arcs (Kinrade et al, 2013;Smith et al, 2008). In the auroral ionosphere the increasing of the fluctuations intensity followed after the auroral activity was observed (Aarons, 1997;Shagimuratov et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The phase scintillation is often collocated with bright auroras (Smith et al, 2008Kinrade et al, 2013, fast-drifting irregularities and steep density gradients in the cusp (Prikryl et al, 2011a), and TOI and patches in the polar cap; more recently, weak to moderate scintillation was observed collocated with SAPS at subauroral latitudes (Prikryl et al, 2013b(Prikryl et al, , 2015b. Interhemispheric comparison of high-latitude ionospheric scintillation during geomagnetic storms has revealed similarities as well as asymmetries between the northern and southern auroral zones, cusps and polar caps (Prikryl et al, 2011b, Kinrade et al, 2012Prikryl et al, 2013a).…”
Section: P Prikryl Et Al: Gps Scintillation -Part 2: Interhemisphermentioning
confidence: 99%
“…One of these concerns the study of the physical processes in the polar region, needed to understand the fundamental aspects of the coupling between the solar wind and the Earth's magnetosphere and ionosphere. The other focuses on the space-related technical applications, as the presence of the ionospheric irregularities can impact variety of trans-ionospheric radio communication and even distort the performance of the global navigation systems (e.g., Smith et al 2008). So, study of morphology and spatio-temporal dynamics of the ionospheric irregularities, their dependences on geophysical factors for proper specification by an empirical model is actual for both fundamental and applied tasks.…”
Section: Introductionmentioning
confidence: 99%